AIDS in the twenty-first century disease and globalization - Barnett, Tony (Palgrave Macmillan, 2006)
First published in 2002, AIDS in the Twenty-First Century met with widespread praise from researchers and policy makers. This edition is fully revised to take account of the latest facts and developments in the field. All statistics and evidence have been updated and their meanings reconsidered. Latest developments in vaccines, anti-retroviral treatments and microbicides are discussed along with information about the President's Emergency Plan for AIDS Relief and The Global Fund to Fight AIDS, Tuberculosis and Malaria.